2017
DOI: 10.1016/j.actamat.2016.11.067
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling deformation mechanisms around FCC and BCC nanocontacts through slip trace and pileup topography analyses

Abstract: Nanocontact loadings offer the potential to investigate crystal plasticity from surface slip trace emissions and distinct pileup patterns where individual atomic terraces arrange into hillocks and symmetric rosettes. Our MD simulations in FCC Cu and Al nanocontacts show development of specific dislocation interception, cross-slip and twin annihilation mechanisms producing traces along characteristic <011> and <112> directions. Although planar slip is stabilized through subsurface dislocation interactions, high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…Here, the lattice constant misfit ( ε ) is defined as the difference of lattice constant between substrate and film materials: ε = ( a substrate − a film )/ a substrate , where a is the lattice constant. The films with a low ε can keep a similar growth orientation of the substrate whereas the films with a large ε prefer to grow on the plane with a minimum surface energy, such as the (111) plane in fcc film, the (110) plane in bcc films, and the (011) plane in Ti and Co films with hcp structure . The simulated films grow in two main modes, namely the Volmer–Weber mode and the Frank–van der Merwe mode resulting from the different diffusion and mobility of various atoms.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, the lattice constant misfit ( ε ) is defined as the difference of lattice constant between substrate and film materials: ε = ( a substrate − a film )/ a substrate , where a is the lattice constant. The films with a low ε can keep a similar growth orientation of the substrate whereas the films with a large ε prefer to grow on the plane with a minimum surface energy, such as the (111) plane in fcc film, the (110) plane in bcc films, and the (011) plane in Ti and Co films with hcp structure . The simulated films grow in two main modes, namely the Volmer–Weber mode and the Frank–van der Merwe mode resulting from the different diffusion and mobility of various atoms.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 shows different motion mechanisms of deposited atoms. [25][26][27] The simulated films grow in two main modes, namely the Volmer-Weber mode and the Frank-van der Merwe mode resulting from the different diffusion and mobility of various atoms. This indicates that resputtering and diffusion are two major motion mechanisms after an atom impingement.…”
Section: The Formation Of Interface and Filmmentioning
confidence: 99%
See 1 more Smart Citation
“…Begau et al [35,36] and Stukowski and Arsenlis [37] also observed the prismatic dislocation loops in their MD simulations. The MD simulations of Varillas et al [38] studied the dislocation interaction, including prismatic loop formation, and identified the formation mechanisms of slip-step and pile-ups in FCC and BCC metals. However, these prismatic loops are not observed by conventional experiments, which have a slow indentation velocity [9,32,[39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…Metallic thin film coatings have attracted considerable attention due to their unique physical, mechanical and thermal properties [ 1 , 2 , 3 ], such as high strength, high hardness and high melting point, etc. Due to these excellent properties, metallic thin film coatings have been widely used in modern industry.…”
Section: Introductionmentioning
confidence: 99%